Design of communication: a review of theories and models - Costa, C. J.; Aparicio, M.; Braga, A. S. (Workshop on Information Systems and Design of Communication, ISDOC 2012, 2012)
Design of communication is a multidisciplinary field. Several theories have been proposed in the context of different fields-from philosophy, mathematics, and physics to literature, economics and psychology. Those theories may support the design of communication. The purpose of this paper is to identify the main communication theories, and to analyze which of them have been employed in the context of design of communication. The main purpose of the framework presented in this paper is to group communication theories into three theoretical perspectives. Several other theories are also presented, illustrating their applicability in the field of the design of communication, which appeared in some of the research papers presented at the SIGDOC conferences and workshops.